Overconfidence and Stock Market Participation of Potential Retail Investor in Indonesia: A Preliminary Study - Justina, Dormauli (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study explores the existence of overconfidence among potential retail investors in Indonesia when deciding to participate in the stock market. The investigation was conducted using a quick survey followed by interviews with two informants. The results indicate that overconfidence in financial literacy does exist in individuals. This study is preliminary, so its results can be used as a basis for further research. A suggested direction for further research is to examine the causal relationship between overconfidence and stock market participation in the Indonesian context.